Zinc complex synthesis and application of zinc complex as fluorescent probe and photodegradation catalyst
Through the fluorescence recognition and photocatalytic functions of zinc complexes, the problem of difficulty in detecting trivalent iron ions, divalent copper ions and nitrofurantoin at the same time and degrading methylene blue dye in the prior art is solved, achieving low-cost and efficient detection and Degradation effect, suitable for industrial applications.
Patent Information
- Application Number
- CN202411339339.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to detect trivalent iron ions, divalent copper ions and nitrofurantoin at the same time, and it also has the function of photodegrading methylene blue dye at the same time. The traditional methods have problems such as low detection efficiency, high cost and complex operation.
The zinc complex is constructed using 3-nitrophthalic acid, 4,4'-bis(2-methylimidazolyl)biphenyl and zinc nitrate hexahydrate to form a zinc complex with fluorescence recognition function, which is used to detect the three Valid iron ions, divalent copper ions and nitrofurantoin and degrade methylene blue dyes as photocatalysts.
It realizes low-cost, easy to operate and efficient detection of trivalent iron ions, divalent copper ions and nitrofurantoin, and efficiently degrades methylene blue dye under visible light, with a degradation rate of 91.44%, suitable for industrial production and environmental monitoring.
Smart Images

Figure CN119219672A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical fields of ion detection, antibiotic detection and dye degradation, and specifically relates to the preparation of a zinc complex with 3-nitrophthalic acid and 4,4'-bis(2-methylimidazolyl)biphenyl as ligands and its application as a fluorescent probe in the detection of trivalent iron ions, divalent copper ions and nitrofurantoin and as a photodegradation catalyst in the degradation of methylene blue dye wastewater. Background Art
[0002] Ferric ions (Fe 3+ ) participates in the composition of multiple enzymes and the immune system in the human body. It is the main component of hemoglobin and participates in many important biochemical reactions in biological cells. Insufficient or excessive iron in the body will cause many diseases. Iron deficiency is an important cause of anemia, hemochromatosis, mental retardation, arthritis, diabetes and other diseases, which affects human health. However, if the iron content in the human body is excessive, it will cause changes in the structure of human organs and lead to lesions; such as liver fibrosis, which can be life-threatening in severe cases. Divalent copper ions (Cu 2+ ) is an important factor affecting copper enzyme proteins in organisms and has important physiological effects on the human body. When the human body lacks or has an excess of copper, diseases will occur and even threaten life. If the human body ingests excessive copper ions, it is easy to cause liver, kidney and gastrointestinal tract related diseases. Copper deficiency can lead to anemia, leukopenia, central nervous system degeneration, low blood iron, low blood copper, and low serum protein syndrome. Therefore, it is very important to quickly, conveniently and accurately detect trivalent iron and divalent copper ions.
[0003] Nitrofurantoin (NFT) is a national essential medicine with a broad-spectrum antibacterial effect. It can effectively kill Gram-positive and Gram-negative bacteria of lower urinary tract infection. It is mainly used clinically for acute lower urinary tract infection, chronic bacteriuria and recurrent chronic urinary tract infection caused by sensitive bacteria. The adverse reactions of nitrofurantoin involve multiple organ systems, including the digestive system: nausea, vomiting, diarrhea, etc.; respiratory system: acute pneumonia, pulmonary interstitial fibrosis, etc.; nervous system: trigeminal neuralgia, peripheral neuropathy and blood system: hemolysis, chronic hemolytic anemia; systemic hypersensitivity reactions: rash, fever, jaundice, liver damage, etc. Based on the above reasons, it is of great research value to realize the selective fluorescence identification of nitrofurantoin.
[0004] Organic dyes refer to a class of organic compounds that can change color under the action of light, heat or chemical reagents. They usually have color and fluorescence properties and can be used to dye various fibers, paper, plastics, etc. Because organic dyes have aromatic ring structures, most dyes are carcinogenic and mutagenic. Therefore, it is urgent to remove dyes from polluted water to maintain human health and protect environmental resources.
[0005] Metal-organic frameworks (MOFs) are porous ordered materials formed by the self-assembly of organic linkers and metal ions or clusters. MOFs materials have pores, exposed metal sites, and active organic groups with Lewis acid or basic sites. They can effectively interact with guest molecules (including anions, metal cations, and organic small molecules) to increase the concentration of the detected guest and improve the detection efficiency. A series of fluorescent probe MOFs materials have been reported, but there are relatively few reports on MOFs materials that can detect multiple guest molecules at the same time. The porosity and large specific surface area of MOFs materials allow dye molecules to pass through the pores quickly, which can improve the efficiency of photocatalytic degradation; the interaction between metal ions and ligands of MOFs materials can effectively separate photogenerated electrons and holes, thereby further improving their photocatalytic activity.
[0006] In summary, MOFs with fluorescence and photodegradation have been widely reported, but MOFs with both fluorescence and photodegradation properties are still lacking. 3+ , Cu 2+ There are very few reports on MOFs materials that respond to both photocatalysis and NFT and have obvious photodegradation dye properties. Summary of the invention
[0007] The present invention aims to provide a zinc complex capable of simultaneously detecting ferric iron, divalent copper, furantoin and degrading methylene blue dye and a preparation method thereof. The present invention selects 3-nitrophthalic acid, 4,4'-bis(2-methylimidazolyl)biphenyl and zinc nitrate hexahydrate to construct the zinc complex. The zinc complex has the function of fluorescent recognition of ferric iron, divalent copper and furantoin, and can effectively detect the presence of trace ferric iron, divalent copper and furantoin contained in aqueous solution, meeting the requirements of low cost, simple operation and high efficiency; the zinc complex can efficiently degrade methylene blue organic dye and can ensure excellent catalytic activity; the zinc complex has a simple synthesis process, low cost, high efficiency, good reproducibility, easy separation, can be applied to industrial production, and has potential application prospects in the fields of environmental monitoring, life sciences and pollutant degradation.
[0008] The chemical formula of the zinc complex capable of simultaneously detecting trivalent iron ions, divalent cupric ions, nitrofurantoin and degrading methylene blue dye involved in the present invention is: [Zn(NPTH)(4,4′-BMIBP)·3H2O], wherein 4,4′-BMIBP=4,4′-bis(2-methylimidazolyl)biphenyl, H2NPTH=3-nitrophthalic acid, and the structural formulas of 4,4′-BMIBP and H2NPTH are as follows:
[0009]
[0010] Furthermore, the structural formula of the zinc complex is:
[0011]
[0012] The crystal of the zinc complex of the present invention belongs to the monoclinic system, its space group is P21 / c, and the unit cell parameters are α=90°, β=97.563(16)°, γ=90°, The smallest asymmetric unit of the complex consists of a zinc ion, a NPTH 2- The anion, a 4,4′-BMIBP ligand and three solvent water molecules that do not participate in the coordination. Figure 1 As shown, each zinc ion and two different NPTH 2- The two oxygen atoms (O1 and O4A) of the ligand are coordinated by the two nitrogen atoms (N1 and N4B) of two different 4,4′-BMIBP ligands to form a tetrahedral {ZnN2O2} configuration (symmetry codes are: A = x, 1 / 2-y, 1 / 2+z; B = -x, -1 / 2+y, 3 / 2-z). In this zinc complex, 3-nitrophthalic acid removes all protons, and the two carboxyl groups are connected to the two zinc ions in a monodentate coordination manner. Adjacent zinc ions are connected by 3-nitrophthalic acid ligands to form a one-dimensional linear [Zn(NPTH)] chain, in which the distance between adjacent zinc ions is ( Figure 2 In addition, adjacent zinc ions are connected through 4,4′-BMIBP ligands to form a one-dimensional zig-zag [Zn(4,4′-BMIBP)] chain, in which the distance between adjacent zinc ions is ( Figure 3 ). Adjacent one-dimensional [Zn(NPTH)] and [Zn(4,4′-BMIBP)] chains are connected to each other through common zinc ions, eventually forming a Figure 4 The two-dimensional planar structure shown.
[0013] The preparation method of the zinc complex involved in the present invention comprises the following steps:
[0014] (1) 4,4′-bis(2-methylimidazolyl)biphenyl, 3-nitrophthalic acid, and zinc nitrate hexahydrate in a molar ratio of 1:1:1 were weighed into a 10 ml polytetrafluoroethylene liner, and a mixed solution of H2O and N,N-dimethylformamide was added to form a mixed solution, and ultrasonication was performed to uniformly disperse the solution; the polytetrafluoroethylene liner was transferred to a 50 ml reaction kettle;
[0015] (2) baking the mixture obtained in step (1) at 100° C. for 72 hours, and naturally cooling to room temperature after the reaction is completed;
[0016] (3) washing the product obtained in step (2) with ethanol for multiple times to obtain colorless block crystals, which are the zinc complex.
[0017] Furthermore, the present invention provides the use of the zinc complex as a fluorescent probe for trivalent iron ions, divalent cupric ions, and furantoin; and provides the use of the zinc complex as a photocatalyst to degrade methylene blue dye wastewater.
[0018] The advantages of the invention are: the preparation method is simple in process, easy to separate, good in reproducibility, can obtain single crystal form, high-purity crystal materials, and is easy to industrialize; the product has the function of fluorescence recognition of trivalent iron ions, divalent copper ions, and furantoin, and can be used for the detection of trace trivalent iron ions, divalent copper ions, and furantoin in aqueous solution. Compared with the traditional detection method, the method has the advantages of quantitative, rapid, sensitive, efficient, simple operation, etc., and the quenching constants are 4.91×10 3 , 1.11×10 4 and 7.22×10 3 ; This product can effectively catalyze the degradation of methylene blue dye under visible light, and the degradation rate of methylene blue is 91.44% in 130 minutes.
[0019] Figure content
[0020] Figure 1 Figure 2 is a diagram of the coordination environment of zinc ions in the zinc complex of the present invention.
[0021] Figure 2 The one-dimensional [Zn(NPTH)] chain structure diagram of the zinc complex of the present invention.
[0022] Figure 3 The one-dimensional [Zn(4,4′-BMIBP)] chain structure diagram of the zinc complex of the present invention.
[0023] Figure 4 It is a two-dimensional structure diagram of the zinc complex of the present invention.
[0024] Figure 5 The figure is the powder XRD pattern of the zinc complex of the present invention.
[0025] Figure 6 It is the thermogravimetric diagram of the zinc complex of the present invention.
[0026] Figure 7 It is the solid fluorescence image of the zinc complex of the present invention.
[0027] Figure 8 The figure is a fluorescence intensity diagram of the zinc complex of the present invention in aqueous solutions of trivalent iron ions at different concentrations.
[0028] Fig. 9 It is a linear fitting spectrum of the fluorescence peak ratio of the zinc complex of the present invention and the concentration of trivalent iron ions.
[0029] Fig.10 The figure is a fluorescence intensity diagram of the zinc complex of the present invention in aqueous solutions of divalent copper ions at different concentrations.
[0030] Fig.11 It is a linear fitting spectrum of the fluorescence peak ratio of the zinc complex of the present invention and the concentration of divalent copper ions.
[0031] Fig.12 The figure is a fluorescence intensity diagram of the zinc complex of the present invention in aqueous nitrofurantoin solutions with different concentrations.
[0032] Fig.13 It is a linear fitting spectrum of the fluorescence peak ratio of the zinc complex of the present invention and the concentration of nitrofurantoin.
[0033] Fig.14 This is a diagram showing the photocatalytic degradation of methylene blue by the zinc complex of the present invention.
[0034] Fig.15 It is the infrared spectrum of the zinc complex of the present invention. DETAILED DESCRIPTION
[0035] In order to better understand the present invention, the content of the present invention is further described below in conjunction with implementation examples, but the content of the present invention is not limited to the following embodiments.
[0036] Example 1: Synthesis of complex
[0037] (1) 3-nitrophthalic acid (0.05 mmol), 4,4′-bis(2-methylimidazolyl)biphenyl (0.05 mmol), and zinc nitrate hexahydrate (0.05 mmol) were weighed into a 10 ml polytetrafluoroethylene liner, 2 ml of the aqueous solution and 0.5 ml of N,N-dimethylformamide solution were added to form a mixed solution, and ultrasonication was performed to uniformly disperse the mixture. The polytetrafluoroethylene liner was then transferred to a 50 ml reaction kettle;
[0038] (2) baking the mixture obtained in step (1) at 100° C. for 72 hours, and naturally cooling to room temperature after the reaction is completed;
[0039] (3) The solid separated in step (2) was washed three times with ethanol to obtain colorless block crystals, which are the zinc complex, with a yield of 78.12%.
[0040] Experimental Example 1: Crystal Structure
[0041] Single crystal X-ray diffraction studies show that the zinc complex synthesized in Example 1 belongs to the monoclinic system, its space group is P21 / c, and the unit cell parameters are α=90°, β=97.563(16)°, γ=90°, The smallest asymmetric unit of the complex consists of a zinc ion, a NPTH 2- The anion, a 4,4′-BMIBP ligand and three solvent water molecules that do not participate in the coordination. Figure 1 As shown, each zinc ion and two different NPTH 2- The two oxygen atoms (O1 and O4A) of the ligand are coordinated by the two nitrogen atoms (N1 and N4B) of two different 4,4′-BMIBP ligands to form a tetrahedral {ZnN2O2} configuration (symmetry codes are: A = x, 1 / 2-y, 1 / 2+z; B = -x, -1 / 2+y, 3 / 2-z). In this zinc complex, 3-nitrophthalic acid removes all protons, and the two carboxyl groups are connected to the two zinc ions in a monodentate coordination manner. Adjacent zinc ions are connected by 3-nitrophthalic acid ligands to form a one-dimensional linear [Zn(NPTH)] chain, in which the distance between adjacent zinc ions is ( Figure 2 In addition, adjacent zinc ions are connected through 4,4′-BMIBP ligands to form a one-dimensional zig-zag [Zn(4,4′-BMIBP)] chain, in which the distance between adjacent zinc ions is ( Figure 3 ). Adjacent one-dimensional [Zn(NPTH)] and [Zn(4,4′-BMIBP)] chains are connected to each other through common zinc ions, eventually forming a Figure 4 The two-dimensional planar structure shown.
[0042] Experimental Example 2: Powder XRD
[0043] The powder X-ray diffraction peaks of the zinc complex synthesized in Example 1 are basically consistent with the theoretical diffraction peaks, indicating that the prepared zinc complex crystals have a high phase purity. Figure 5 shown.
[0044] Experimental Example 3: Thermogravimetric Analysis
[0045] Thermogravimetric analysis of the zinc complex obtained in Example 1 was performed using a thermogravimetric analyzer to obtain Figure 6 Thermogravimetric diagram shown. Figure 6 It can be seen that in the range of 30-160°C, a weight loss of 7.38% occurs (theoretical value is 8.41%), and this part of the weight loss is mainly caused by the removal of solvent water molecules that do not participate in coordination; the second weight loss occurs in the temperature range above 260°C, and this part of the weight loss is mainly caused by the thermal decomposition of 4,4′-bis(2-methylimidazolyl)biphenyl and 3-nitrophthalic acid.
[0046] Experimental Example 4: Solid Fluorescence Properties
[0047] The solid fluorescence properties of the zinc complex obtained in Example 1 were tested using a fluorescence spectrometer, and the results were Figure 7 The solid fluorescence diagram shown shows that the excitation peak of the zinc complex is 246 nanometers, and the emission peak is 356 nanometers.
[0048] Experimental Example 5: Fluorescence Detection of Ferric Ions
[0049] By measuring the fluorescence spectrum of the zinc complex obtained in Example 1 in aqueous solutions of trivalent iron ions at different concentrations, Figure 8 From the fluorescence emission spectrum shown, it can be seen that the fluorescence intensity gradually decreases with the increase of the concentration of trivalent iron ions, showing an obvious fluorescence quenching effect, which can be used to detect the concentration of trivalent iron ions in aqueous solution.
[0050] Using the Stern-Volmer equation (I0 / I=1+K sv [M]) calculated the relationship between the relative change ratio of fluorescence intensity (I0 / I) and the concentration of trivalent iron ions, and plotted Fig. 9 The SV graph shown is a linear fitting curve of the relative change ratio of fluorescence intensity and the concentration of trivalent iron ions. It can be seen that the two are linearly related in the low concentration range, and the quenching constant K sV is 4.91×10 3 .
[0051] Experimental Example 6: Fluorescence Detection of Divalent Copper Ions
[0052] By measuring the fluorescence spectra of the zinc complex obtained in Example 1 in aqueous solutions of divalent copper ions at different concentrations, Fig.10 From the fluorescence emission spectrum shown, it can be seen that the fluorescence intensity gradually decreases with the increase of divalent copper ion concentration, showing an obvious fluorescence quenching effect, which can be used to detect the concentration of divalent copper ions in aqueous solution.
[0053] Using the Stern-Volmer equation (I0 / I=1+K sv [M]) calculated the relationship between the relative change ratio of fluorescence intensity (I0 / I) and the concentration of divalent copper ions, and plotted Fig.11 The SV graph shown is a linear fitting curve of the relative change ratio of fluorescence intensity and the concentration of divalent copper ions. It can be seen that the two are linearly related in the low concentration range, and the quenching constant K sV 1.11×10 4 .
[0054] Experimental Example 7: Fluorescence Detection of Nitrofurantoin
[0055] By measuring the fluorescence spectrum of the zinc complex obtained in Example 1 in aqueous solutions of nitrofurantoin at different concentrations, the following results were obtained: Fig.12As shown in the fluorescence emission spectrum, it can be seen that the fluorescence intensity gradually decreases with the increase of furantoin concentration, showing an obvious fluorescence quenching effect, indicating that the zinc complex can detect the concentration of furantoin in aqueous solution.
[0056] The relationship between the relative change ratio of fluorescence intensity (I0 / I) and the concentration of nitrofurantoin was calculated using the Stern-Volmer equation and plotted. Fig.13 The SV graph shown is a linear fitting curve of the relative change ratio of fluorescence intensity and nitrofurantoin concentration. It can be seen that the two are linearly related in the low concentration range, and the quenching constant K sV 7.22×10 3 .
[0057] Experimental Example 8: Photodegradation of methylene blue dye
[0058] 30 mg of the zinc complex obtained in Example 1 was weighed and added to 50 ml of a methylene blue aqueous solution (10 mg / L), and then 5 μl of hydrogen peroxide was added. The mixture was stirred in the dark for 30 minutes to allow the surface of the zinc complex to reach adsorption-desorption equilibrium. The mixture was then irradiated with a visible light while stirring at an intensity of 300 watts, room temperature, and a pH of about 7. 1 ml of the methylene blue aqueous solution was taken every 10 minutes, and the absorbance change was immediately tested. The photodegradation results showed that the degradation rate of the complex for methylene blue in 130 minutes was 91.44% (as shown in Figure 2). Fig.14 ).
Claims
1. A zinc complex capable of simultaneously detecting ferric ions, divalent cupric ions, nitrofurantoin and methylene blue dye wastewater, characterized in that: Its chemical formula is [Zn(NPTH)(4,4′-BMIBP)·3H2O], wherein 4,4′-BMIBP=4,4′-bis(2-methylimidazolyl)biphenyl, H2NPTH=3-nitrophthalic acid; the zinc complex belongs to the monoclinic system, its space group is P21 / c, and the unit cell parameters are α=90°, β=97.563(16)°, γ=90°, The smallest asymmetric unit of the zinc complex consists of a zinc ion, a NPTH 2- ion, a 4,4′-BMIBP ligand and three solvent water molecules; the zinc complex is a two-dimensional planar structure, and the zinc ion in the molecule adopts a four-coordination mode to form a tetrahedral configuration structure of {ZnN2O2}.
2. The method for preparing the zinc complex according to claim 1, characterized in that: 3-nitrophthalic acid (0.05 mmol), 4,4′-bis(2-methylimidazolyl)biphenyl (0.05 mmol), and zinc nitrate hexahydrate (0.05 mmol) were weighed into a 10 ml polytetrafluoroethylene liner, and 2 ml of an aqueous solution and 0.5 ml of a N,N-dimethylformamide solution were added to form a mixed solution, which was evenly dispersed by ultrasound. Finally, the polytetrafluoroethylene liner was transferred to a 50 ml reactor, and the reaction was carried out for three days under sealed conditions and a constant temperature of 100°C. The mixture was then naturally cooled to room temperature and filtered and washed to obtain colorless block crystals.
3. A zinc complex as claimed in claim 1 or a zinc complex prepared by the method as claimed in claim 2 as a fluorescent probe for detecting trivalent iron ions (Fe 3+ ), divalent copper ion (Cu 2+ ) and its application in the field of nitrofurantoin (NFT).
4. A use according to claim 3, characterized in that: The linear fitting curve equation of the relative change ratio of the fluorescence intensity of the zinc complex and the concentration of trivalent iron ions is: I0 / I=4910[Fe 3+ ]+0.9999; the linear fitting curve equation of the relative change ratio of the fluorescence intensity of the zinc complex and the concentration of divalent copper ions is: I0 / I=11180[Cu 2+ ]+0.9989; the linear fitting curve equation of the relative change ratio of the fluorescence intensity of the zinc complex and the concentration of nitrofurantoin is: I0 / I=7220[NFT]+0.9986.
5. Use of the zinc complex as claimed in claim 1 or the zinc complex prepared by the method as claimed in claim 2 in the field of photocatalytic degradation of dye molecules.
6. The use according to claim 5, characterized in that: The dye molecule is methylene blue, and the degradation rate of methylene blue by the zinc complex in 130 minutes is 91.44%.
Citation Information
Cited By
Zn-TIB-BDC crystal and preparation method and application thereof
CN122608904A